Degradación de cianuro en efluente de lixiviación de minerales auríferos, mediante Pseudomonas pseudoalcaligenes nativas - Arias Arce, Vladimir Alejandro (2024)
The generation of cyanide-containing tailings is increasing, so the search for methodologies and microorganisms to counteract the negative action to the detriment of the environment is incessant. The present study was carried out with strains of Pseudomonas pseudoalcaligenes isolated from effluents of the gold ore cyanidation process. First, tolerance tests were performed in solutions with 250 ppm sodium cyanide at different pH values, using an initial population of 4.00E+07 CFU/mL and agitated for a period of 54 hours; degradation up to 39.2% free cyanide (CN-) was observed at a pH of 9.8. Then, in the CN- degradation for 144 hours, in media consisting of cyanidation process effluent solution at pH 10.5, with an initial bacterial population of 9.94E+08 CFU/mL and at concentrations of 80 to 700 ppm of CN-, reductions of 55.89 to 84.79 % of cyanide were obtained, expressed with the equations: y80 = -0.2393x + 73.05 and y700 = -3.6439x + 617.98, respectively. It was determined that the degradation of cyanide is directly related to the cyanide content in the solution; that is, the higher the cyanide concentration, the higher the abatement